2013
DOI: 10.1038/npp.2013.229
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-Induced Changes of Synaptic Transmission in the Striatum are Modulated by Adenosine A2A Receptors and Involve the Tyrosine Phosphatase STEP

Abstract: The striatum is a brain area implicated in the pharmacological action of drugs of abuse. Adenosine A 2A receptors (A 2A Rs) are highly expressed in the striatum and mediate, at least in part, cocaine-induced psychomotor effects in vivo. Here we studied the synaptic mechanisms implicated in the pharmacological action of cocaine in the striatum and investigated the influence of A 2A Rs. We found that synaptic transmission was depressed in corticostriatal slices after perfusion with cocaine (10 mM). This effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 46 publications
(62 reference statements)
4
33
0
Order By: Relevance
“…In addition, mGluR activation has been shown to induce rapid translation of striatal-enriched protein tyrosine phosphatase (STEP), which also downregulates AMPAR surface expression and may actively maintain endocytosis rates (Luscher and Huber, 2010;Zhang et al, 2008). Acute exposure to both amphetamine and cocaine alters phosphorylation of STEP in striatal regions and inactivation of STEP prevents cocaineinduced reductions in AMPAR-mediated currents in MSNs (Chiodi et al, 2014;Sun et al, 2007;Tashev et al, 2009;Valjent et al, 2005). However, the degree to which alterations in STEP activity may occur in response to psychostimulant re-exposure is unknown.…”
Section: Mechanisms Underlying Synaptic Depotentiationmentioning
confidence: 99%
“…In addition, mGluR activation has been shown to induce rapid translation of striatal-enriched protein tyrosine phosphatase (STEP), which also downregulates AMPAR surface expression and may actively maintain endocytosis rates (Luscher and Huber, 2010;Zhang et al, 2008). Acute exposure to both amphetamine and cocaine alters phosphorylation of STEP in striatal regions and inactivation of STEP prevents cocaineinduced reductions in AMPAR-mediated currents in MSNs (Chiodi et al, 2014;Sun et al, 2007;Tashev et al, 2009;Valjent et al, 2005). However, the degree to which alterations in STEP activity may occur in response to psychostimulant re-exposure is unknown.…”
Section: Mechanisms Underlying Synaptic Depotentiationmentioning
confidence: 99%
“…In an earlier paper, these investigators (Chiodi et al, ) found that activation of the G protein coupled A 2A R activates STEP leading to a reduction in striatal field potential amplitude (i.e., an increase in synaptic depression). The reduction in field potential amplitude can be blocked by D 2 R antagonists, A 2A R antagonists, non‐selective protein tyrosine phosphatase inhibitors, or calcineurin inhibitors.…”
mentioning
confidence: 99%
“…Likewise, knockout of the mouse A 2A R also prevented the cocaine‐induced reduction in striatal field potential amplitude. When recording whole‐cell currents from medium spiny neurons in the dorsal striatum, Chiodi et al () observed that cocaine reduced AMPA‐ and NMDA‐mediated excitatory post‐synaptic currents. The cocaine‐induced reduction in excitatory post‐synaptic currents was blocked with a A 2A R antagonist or STEP substrate trapping mutant, TAT‐STEP, illustrating the important role of A 2A R and STEP in this pathway that leads to synaptic depression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9-11 STEP is also associated with the negative regulation of extracellular regulated kinase (ERK), which is a member of the MAPK family and functions critically in synaptic strengthening. In addition, it was shown that cocaine administration led to increase STEP activity in the striatum, which resulted in synaptic depression in that brain area, 17,18 suggesting that STEP inhibitors can be used to treat or mitigate symptoms caused by cocaine abuse. 11 Consistently, a dramatic upregulation of ERK activity was observed in a ptpn5 knockout mouse model.…”
Section: Introductionmentioning
confidence: 99%